Hypothermia prevention during surgery: comparison between thermal mattress and thermal blanket - Moyses, Ariane Marques [UNESP]; Trettene, Armando dos Santos; Camacho Navarro, Lais Helena [UNESP]; Ayres, Jairo Aparecido [UNESP] (Universidade de São Paulo (USP), 2014)
This study aimed to compare the efficiency of the thermal blanket and thermal mattress in the prevention of hypothermia during surgery. Thirty-eight randomized patients were divided into two groups (G1 - thermal blanket and G2 - thermal mattress). The variables studied were: length of surgery, length of stay in the post-anesthetic care unit, period without using the device after thermal induction, transport time from the operating room to post-anesthetic care unit, intraoperative fluid infusion, surgery size, anesthetic technique, age, body mass index, esophageal, axillary and operating room temperature. In G2, length of surgery and starch infusion longer was higher (both p=0.03), but no hypothermia occurred. During the surgical anesthetic procedure, the axillary temperature was higher at 120 minutes (p=0.04), and esophageal temperature was higher at 120 (p=0.002) and 180 minutes (p=0.03) and at the end of the procedure (p=0.002). The thermal mattress was more effective in preventing hypothermia during surgery.
Keywords: Hypothermia; Perioperative period; Perioperative nursing; Postanesthesia nursing